Nivolumab Versus Regorafenib in Patients With Hepatocellular Carcinoma After Sorafenib Failure - Kuo, Yuan-Hung; Yen, Yi-Hao; Chen, Yen-Yang; Kee, Kwong-Ming; Hung, Chao-Hung; Lu, Sheng-Nan; Hu, Tsung-Hui; Chen, Chien-Hung; Wang, Jing-Houng (Frontiers in Oncology, 2021)
Background Nivolumab and regorafenib are approved second-line therapies for patients with hepatocellular carcinoma (HCC) after sorafenib failure. This study compared the effectiveness of nivolumab and regorafenib following sorafenib. Methods We retrospectively enrolled HCC patients who had undergone nivolumab or regorafenib after sorafenib failure. Treatment response, treatment-related adverse events (TRAE) and clinical outcomes of study patients were recorded and analyzed. Results A total of 90 patients (male/female: 67/23, mean age: 63 years) were enrolled, including 32 patients in the Nivolumab group and 58 patients in the Regorafenib group. The Nivolumab group had better objective response rates (16% vs 6.4%) and disease control rates (44% vs 31.9%) than the Regorafenib group, but there was no statistical difference. The comparison of time to progression (3.0 months vs 2.6 months, p=0.786) and overall survival (OS) (14 months vs 11 months, p = 0.763) between Nivolumab and Regorafenib groups were also insignificant. Regarding number of TRAE incidences, the Nivolumab group was significantly lower than the Regorafenib group (37.5% vs 68%). After cession of nivolumab/regorafenib, 34 patients (37.8%) (Nivolumab group/Regorafenib group: 11/23) could afford the following therapies. Concerning sequential systemic therapies, 17 patients (18.9%) received third-line therapy, whereas six patients (6.7%) could move to fourth-line therapy. In multivariable analysis, patients who achieved disease control were associated with improved OS (hazard ratio, 0.18; 95% confidence interval, 0.07–0.46; p<0.001) after adjusting Child-Pugh class and post-treatment. Conclusions After sorafenib failure, using nivolumab or regorafenib both illustrated promising treatment outcomes.